1998
DOI: 10.1002/(sici)1096-8652(199805)58:1<72::aid-ajh13>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Hemophilia B in a female carrier due to skewed inactivation of the normal X-chromosome

Abstract: A novel missense mutation (codon 351, GCT (Ala) --> CCT (Pro)) of the FIX gene was characterised in a young female with mild hemophilia B. She is heterozygous for the FIX mutation inherited from her carrier mother. Analysis of the methyl-sensitive Hpa II sites at the 5' end of the hypoxanthine phosphoribosyltransferase gene showed that skewed inactivation of the X chromosome carrying her normal FIX gene accounted for the hemophilia phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Nonrandom X inactivation was reported in occasional females with clinical manifestations of various X-linked diseases, such as Fabry disease [Ropers et al, 1977;Redonnet-Vernhet et al, 1996], Duchenne muscular dystrophy [Richards et al, 1990;Lupski et al, 1991;Azofeifa et al, 1995], hemophilia B [Schroder et al, 1997;Chan et al, 1998], and Wiscott-Aldrich syndrome [Parolini et al, 1998]. These females were chromosomally normal as was the case in the woman we described and presumably had a mutant copy of the gene for these disorders on an X chromosome that was active in most of their cells.…”
Section: Discussionsupporting
confidence: 53%
“…Nonrandom X inactivation was reported in occasional females with clinical manifestations of various X-linked diseases, such as Fabry disease [Ropers et al, 1977;Redonnet-Vernhet et al, 1996], Duchenne muscular dystrophy [Richards et al, 1990;Lupski et al, 1991;Azofeifa et al, 1995], hemophilia B [Schroder et al, 1997;Chan et al, 1998], and Wiscott-Aldrich syndrome [Parolini et al, 1998]. These females were chromosomally normal as was the case in the woman we described and presumably had a mutant copy of the gene for these disorders on an X chromosome that was active in most of their cells.…”
Section: Discussionsupporting
confidence: 53%
“…Missense changes involving the Cysteine–Alanine–Glycine residues either of the other serine proteases of the coagulation system or of F11 have been described. 28–38 Therefore, we speculated that p.Ala561Asp, when present in homozygosity or in trans , could influence plasmatic levels and/or bleeding tendency. In the present study, bleeding episodes were not recorded in the proband P10, who showed p.Phe301Leu combined with the c.595+3 A>G, whereas bleeding complications were reported when this missense mutation is combined with p.Trp519* (P11 and P12), as previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Since factor IX is smaller than albumin, it distributes in both the extra vascular and intra vascular compartments [2]. Characterization of a young female with mild hemophilia B is a novel missense mutation (codon 351, GCT (Ala) → CCT (Pro) of the FIX gene [8]. Menorrhagia therefore, a life threatening hidden disorder can be unusually due to severe and unexpected inherited bleeding disorder with a very high mortality rate if unchecked needs precise screening of coagulation disorder.…”
Section: Discussionmentioning
confidence: 99%